PTU-218 Prophylactic mesh repair for the prevention of parastomal herniation: a case controlled comparative study between the prophylactic mesh and non-mesh group. (22nd June 2015) - Anwar, S; Bilkhu, A
Abstract : Introduction: To ascertain whether prophylactic mesh reinforcement at the time of stoma formation with a composite synthetic mesh reduces the incidence of parastomal herniation. Method: Data was prospectively collected over 5 years from 1 st January 2009 to 31 st December 2013 for patients undergoing a prophylactic re-enforcement of the para-stomal abdominal wall with a Dynamesh-IPOM mesh, using a laparoscopic intra-peritoneal onlay technique. A case controlled comparison was carried out with a cohort of matched patients undergoing stoma-forming procedures in the same time duration, without the use of a prophylactic mesh. The primary outcome was the development of a parastomal hernia on clinical or radiological examination. Statistical analysis was carried out on IBM SPSS v21 in order to compare age, gender, BMI, ASA, operative time, length of stay, length of follow-up and incidence of hernias in between groups using a single-centre, single-surgeon case-control study design. Results: Eleven patients underwent prophylactic mesh reinforcement of their colostomy using a keyhole mesh configuration (mean age 67 ± 11.9, M:F 8:3, median BMI 29 [95% CI 23–34]. Median operative time was 300 mins [95% CI 205–337]. This group included 8 APER and 3 Hartmann's procedures; there was one conversion to an open procedure. After a median follow-up of 20 months [95% CI 6–27] none developed a parastomal hernia. There were 19 patients in the control group (Mean age 72.4 ± 14.0, M:F 12:7, median BMI 27.1 [95% CI 21.8–37.3]. The median operative time was 300 [95% CI 230–435]. This group included 13 APER, 5 Hartmann's and one left hemicolectomy with end colostomy. There was one conversion to an open procedure. After a median follow-up 15 months [95% CI 6–29] six patients (31.6%) developed a parastomal hernia (two detected on CT scanning and 4 evident on clinical examinations). Two of these went on to have subsequent repair of the hernia (one elective, one emergency). There were no significant differences in between groups for age, gender, ASA, BMI, operative time, rate of conversion and length of follow-up. The likelihood ratio for developing a parastomal hernia was 6.33 ( p < 0 .05) and a Chi-square test demonstrated a significant association of herniation without mesh reinforcement; x 2 (1) = 4.34, p < 0 .05. Conclusion: Prophylactic mesh reinforcement of stomas with a composite synthetic mesh using an intraperitoneal onlay technique caused a significant reduction in the risk of parastomal herniation. Furthermore, the use of this particular synthetic mesh does not confer any additional infective complications. Disclosure of interest: None Declared.